Perception of parental bonds and family functioning in drug-dependent subjects. A resource to explore in the rehabilitation process - Rosas García, Benito (2014)
Parenting styles and the type of family functioning have been linked by many experts in the field of drug addiction to the origin of emotional problems. The aim of this study focuses on the perception of drug addicts on patterns of aging parents; and the perception of family functioning between the child and their parents. For this study three groups were formed: a first group consisting of a sample of 107 male drug addicts subjects (mean age 32,38) This group have supplied a questionnaire socio - demographic, the Parental Bonding Instrument (PBI) and the Family Adaptability and Cohesion Evaluation Scale (FACES III). A second group of 109 male college students (mean age 27,16), which we applied the GDP. A third group of 26 pairs of parents that they applied the FACES III. The results emphasize the following: according to the GDP, drug addicts perceive their parents as higher on overprotection and low care, with the group of college students. Predominates in families of drug addicts a link of “control without affection.” Regarding the FACES III, as evidenced addicts perceive their own family of origin and strongly “detached” in the affective and “chaotic” up in their family structure. Furthermore, the results of the perception of family members (father, mother and son), evidence that drug addicts have children perceived family system characterized by a lack of affection, that contrasts with the perception of parents who have a more cohesive view of the family.